The Effect of Accessibility Improvement on Tourist Excursion Behaviors: Empirical Case Studies in Japan - Kazuo Nishii; Katsunao Kondo; Kuniaki Sasaki (European Regional Science Association (ERSA), 2010)
One of the most important issues in a current situation in tourism in Japan is to identify how attractive cities or towns we can provide visiting tourists as a tourism product satisfying needs and wants. It is therefore necessary to grasp what kind of needs and wants potential tourists can obtain from their experience of visiting cities. For this purpose, an area marketing and management approach (AMMA) is expected to be effective one. In this paper a basic framework of our AMMA will be introduced. In addition, a practical procedure for quantitatively measuring the effect of accessibility improvement on tourist travel demand and activity patterns will be proposed. This paper discusses a practical method for measuring accessibility improvement effect focusing on the increase of the number of visitors to the tourism areas where the level of service in accessing transport facilities is planning to be improved. Two case studies in Japan will be presented in this paper.
Keywords: 330